Trends of Diagnostic and Surgery of Intraocular Foreign Body: a 20 Years Review: Oral Presentation - Observational Study - General practitioner - Nadya Eunice Sumolang; Venny D. Yolanda; Muhammad Ihsan (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Intraocular foreign bodies remain a common cause of ocular emergencies worldwide. Early and proper diagnostics and management are needed to reduce morbidity. In this paper, we reviewed the diagnostic and surgery trends of IOFB in the last 20 years. We aim to serve the update and better understand how to manage cases of IOFBs properly. Methods : We conducted a literature review on Scopus from 2002 to 2022 using the PRISMA method (assisted by the Watase UAKE application). We include imaging and surgery data in cases of metallic and non- metallic IOFB in the anterior, intralenticular, and posterior segments. Results : Thirty-one studies were included from Scopus and reference digging. We then classified the study into two main topics, surgery and diagnostic. In the last 20 years, imaging in diagnosis has been beneficial. CT-scan and MRI are still the leading options in visualizing metallic and non-metallic IOFB, respectively. However, in the case of tiny IOFB, MRI might be performed to visualize the metallic component with special considerations. IOCT also be considered to ensure no IOFB is left behind after removal. As for surgery, combining IOFB removal with pars plana vitrectomy remains the primary choice for IOFB in the posterior segment, combined with phacoemulsification and IOL implantation for the intralenticular and magnetic for the anterior segment. Combining two or more surgical techniques improves outcomes and prevents postoperative complications. Conclusion : A proper understanding of the components, location, and size of IOFB is required to determine the use of practical examinations and management of IOFB cases.